Measuring grit, self-efficacy, curiosity, and intolerance of uncertainty in first-generation college and first-generation osteopathic medical students - Jones, DeWitt; McCalla, Monet; Beverly, Elizabeth A. (BMC Medical Education, 2023)
Medical school is a challenging time, with many medical students reporting symptoms of burnout, depression, anxiety, suicidal ideation, and psychological distress during pre-clinical and clinical years. First-generation college and first-generation medical students may be two groups of students at increased risk for the negative psychosocial effects of medical school. Importantly, grit, self-efficacy, and curiosity are protective factors against the negative psychosocial effects of medical school, whereas intolerance of uncertainty is a risk factor. Thus, research examining the associations among grit, self-efficacy, curiosity, and intolerance of uncertainty in first-generation college and first-generation medical students is needed.